Jejunoileal Atresia in Association with a Multiple Gastrointestinal (GL-) Fistulate (Journal of Science and Technology, 2016)
A long segment jejunoileal atresia in association with multiple internal GI-fistulas and mimicking Hirschsprung’s Disease in a six months old male infant with failure to thrive since birth is reported. In analogy to a liquid reticulation system and utilizing principles of fluid mechanics, the case of atresia and the clinical features of the case presented here are attributed to altered channeling and the rate as well as direction of flow of the intestinal contents. The usually mono-chambered GI-tract is converted into a multi-channeled system by the multiple fistulas through a parallel diversion. Complications and therapeutic uses of parallel diversions of GI- tract diversions have also been discussed.